ON THE DEFORMATION ANALYSIS OF FRAMES OF INELASTIC CONSTITUENTS - A A Rochev (Structural Mechanics of Engineering Constructions and Buildings, 2014)
In this paper, the problem of the deformation calculation of compressed-bent frame of the inelastic elements of the composite having a variable cross section and variable stiffness along the length of shear ties was solved. The solution is based on the theory of elastic composite bars of A.R Rzhanitzin. Statically indetermination of frames is disclosed by the deformation method. Reactions in the input connections are determined by the method of initial parameters. Stiffness of the composite elements is determined using the expression for the determination of equivalence of deformation coefficient, previously obtained by the author, which takes into account the compressibility of the branches, shear deformations of the material of branches forming the bar, the development of inelastic deformation in them